2017
DOI: 10.1074/jbc.m116.764696
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions in PBP2b from β-Lactam-resistant Streptococcus pneumoniae Have Different Effects on Enzymatic Activity and Drug Reactivity

Abstract: Edited by Gerald W. HartPneumococcus resists ␤-lactams by expressing variants of its target enzymes, the penicillin-binding proteins (PBPs), with many amino acid substitutions. Up to 10% of the sequence can be modified. These altered PBPs have a much reduced reactivity with the drugs but retain their physiological activity of crosslinking the peptidoglycan, the major constituent of the bacterial cell wall. However, because ␤-lactams are chemical and structural mimics of the natural substrate, resistance mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…All strains with Thr-445-Ala substitution showed penicillin MIC ≥ 0.25 µg/mL, consistent with a recent work reporting this mutation to reduce PBP binding affinity by 60% and resulting in raised penicillin MIC (>0.25 µg/mL) [26]. Additional mutations beyond the active sites of PBP2b observed in this study had been reported to decrease β-lactams reactivity and is commonly present in strains with penicillin MIC > 0.5 µg/mL [27]. The most common mutations in PBP2x (Thr-338-Ala in STMK motif and Leu-546-Val adjacent to KSG motif) were identified in S. pneumoniae strains exhibiting raised penicillin MICs (2-8 µg/mL), consistent with previous reports associating these mutations with higher-level β-lactam resistance [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…All strains with Thr-445-Ala substitution showed penicillin MIC ≥ 0.25 µg/mL, consistent with a recent work reporting this mutation to reduce PBP binding affinity by 60% and resulting in raised penicillin MIC (>0.25 µg/mL) [26]. Additional mutations beyond the active sites of PBP2b observed in this study had been reported to decrease β-lactams reactivity and is commonly present in strains with penicillin MIC > 0.5 µg/mL [27]. The most common mutations in PBP2x (Thr-338-Ala in STMK motif and Leu-546-Val adjacent to KSG motif) were identified in S. pneumoniae strains exhibiting raised penicillin MICs (2-8 µg/mL), consistent with previous reports associating these mutations with higher-level β-lactam resistance [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…It is notable that mutations in MraY—which are generally last to occur, and never occur alone—might have a compensatory effect. Altered PBPs, while conferring resistance, might be less active transpeptidases than their wild-type counterparts [ 54 ]. For example, the amidotransferase enzyme encoded by murT enables cross-linking of cell wall peptidoglycans by preparing lipid II used by pneumococcal PBPs [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The difference between PBP1b and PBP2x labeling intensity for 7MTz and 7TCO also indicate that protein environment can have a strong effect on bioorthogonal labeling efficiencies. PBP TP active sites are highly structurally homologous, but differences in antibiotic binding between PBPs, along with limited available structural comparisons, suggest that there are subtle differences in active site architecture between PBP isoforms [8,9,12,53–56] . Further structural characterization of PBPs in complex with β‐lactone probes will be necessary to achieve a structure‐based understanding of differences in labeling efficiency.…”
Section: Resultsmentioning
confidence: 99%